2004
DOI: 10.1093/sleep/27.3.551
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Surgery of the Soft Palate in the Treatment of Snoring: a Review of the Literature

Abstract: According to all of the published material, radiofrequency surgery of the soft palate leads to a significant reduction of subjective snoring, and snoring is reduced to a tolerable level. Nevertheless, these findings will have to be confirmed by controlled clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 28 publications
1
27
0
2
Order By: Relevance
“…Our results showed low morbidity and pain. The disadvantages of these techniques are the need for repeated surgical procedures, the fact that they are not useful to treat apnea, their limitation in the selection of patients, and in the case of radiofrequency ablation, cost [12,13] . Our results showing a decline in snoring intensity on the VAS from 8.9 8 0.69 to 4.06 8 1.4 can be compared with other studies that have used the VAS with patients treated with radiofrequency ablation alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results showed low morbidity and pain. The disadvantages of these techniques are the need for repeated surgical procedures, the fact that they are not useful to treat apnea, their limitation in the selection of patients, and in the case of radiofrequency ablation, cost [12,13] . Our results showing a decline in snoring intensity on the VAS from 8.9 8 0.69 to 4.06 8 1.4 can be compared with other studies that have used the VAS with patients treated with radiofrequency ablation alone.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the sclerosing agent instead of the more expensive nonsterilizable radiofrequency device results in a significant economic saving [13] . The price of the generator is about EUR 6,000, the sclerosing agent costs EUR 9 and the device is reusable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from conservative treatment options, many different surgical procedures are offered such as laser-assisted uvuloplasty [10], uvulopalatopharyngoplasty [7,8] or radiofrequency surgery [14][15][16][17][18][19]. Initially, radiofrequency surgery of the soft palate seemed to be promising in the treatment of primary snoring, most recent results of a placebo-controlled study however showed that the reduction of snoring scores that may be achieved is only moderate [19].…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous approaches to find an adequate surgical treatment for primary snoring, no gold standard exists. Various kinds of surgical procedures are available, most of which have been developed for the treatment of obstructive sleep apnea (OSA): uvulopalatopharyngoplasty [7,8], tonsillectomy [9], laser-assisted uvulopalatoplasty [10], uvulaflap [11,12], soft palate implants [13], or radiofrequency surgery of the tongue base or the soft palate [14][15][16][17][18][19]. Some of these procedures are rather invasive and connected with side effects such as post-operative pain or bleeding or persistent swallowing difficulties [20], whereas others show only moderate efficacy [19].…”
Section: Introductionmentioning
confidence: 99%